2016
DOI: 10.9775/kvfd.2016.15008
|View full text |Cite
|
Sign up to set email alerts
|

Usnik Asitin Broylerlerdeki Anticoccidial Etkinliği

Abstract: This experiment was conducted to investigate if usnic acid, a lichen metabolite, exerts therapeutic action against coccidiosis. A total of 160 one-day-old male Ross 308 broiler chicks were divided into 5 experimental groups (A-E), each replicated in 4 pens of 8 chicks. At 16 days of age Groups B-E were infected orally with a mixture of purified oocysts including 30 x 10 4 sporulated oocysts from field isolates of E. acervulina, E. brunetti, E. maxima, E. mitis, E. praecox and E. tenella, whereas Group A was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Authors reported that 100 mg/kg dose of UA exhibited anticoccidial activity compared to toltrazuril. 12 …”
Section: Pharmacological Activities Of Lichensmentioning
confidence: 99%
“…Authors reported that 100 mg/kg dose of UA exhibited anticoccidial activity compared to toltrazuril. 12 …”
Section: Pharmacological Activities Of Lichensmentioning
confidence: 99%